REDESIGN LOGO PABRIK TAHU “CNG” KOTA SOLOK - ROMI ABDHAL, Hendra Afriwan, S. Sn., M. Sn San Ahdi, S.Sn., M.Ds (DEKAVE : Jurnal Desain Komunikasi Visual, 2015)
Pabrik Tahu "CNG" is the largest producer tofu in Solok, which is located at Jl. Sersan Basir No. 6, Gawan, Tanah Garam, the town of Solok. Was established on June 1, 2002, under the leadership of Janisar Can Dt. Rajo Bangkeh.Redesign is a method of redesigning the logo to tofu CNG, the redesign was based on the existing logo does not represent the background and objectives of the company, as well as the absence of a characteristic that differentiates it from other corporate identity. Methods of data analysis are SWOT analysis as in the design of the writer redesign the existing logo design, with consideration of strengths, weaknesses, opportunities, and threats that a comparison between the new logo, the old logo and the logo of a competitor.The new logo design is taken from concept Pabrik Tahu "CNG" name, the name is an abbreviation of Caniago CNG, which is one of the tribes in Minangkabau. The design is based on the concept of mind mapping are finding Datuak, soft and thick, reinforced the concept Datuak company owner who is a tribal Datuak in Caniago. Soft and thick taken of excellence tofu CNG.The main design is the logo, the main media used in the logo redesign tofu CNG that the media stationery sets such as sales invoices, business cards, stamps, costumes and operational cars as well as packaging and manual book. Media support including neon, x-banner, pins and caps.Keywords: Logo Redesign, CNG, Media.